2021
DOI: 10.1016/j.heliyon.2021.e06818
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural commercialisation, poverty reduction and pro-poor growth: evidence from commercial agricultural development project in Nigeria

Abstract: Commercial Agriculture Development is widely seen as a pathway to agriculture commercialization, poverty reduction and pro-poor growth in developing economies. Using a counterfactual approach, this study assessed the impact of the Commercial Agricultural Development Project (CADP) in Nigeria on poverty status of beneficiaries and non-beneficiaries; determine its impact on commercialization of beneficiaries and non-beneficiaries and ascertain the pro-poor impact of the Project. Data from 1199 households compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
(44 reference statements)
1
14
0
Order By: Relevance
“…Previous Studies: Finding of some studies e.g. ; Sanchez et al, 2022;Ojong et al, 2022;Etuk & Ayuk, 2021;Ma et al, 2021;Christiaensen & Martin, 2018;Rapsomanikis, 2015;Collier & Dercon, 2014;Christiaensen et al, 2011;Dercon, 2009;Datt andRavallion, 1998 andVon Braun, 1995 revealed that agricultural commercialisation can be a source of poverty reducing, whereas it aims at adopting agriculture not only to produce food for family's consumption, but also for generating better income by professional applying of technologies and machinery that leads to rising agricultural productivity. The Productivity includes agricultural land and labour which both together are more effective at increasing the incomes of small farmers and poor households who are involved in family farming.…”
Section: Introductionmentioning
confidence: 99%
“…Previous Studies: Finding of some studies e.g. ; Sanchez et al, 2022;Ojong et al, 2022;Etuk & Ayuk, 2021;Ma et al, 2021;Christiaensen & Martin, 2018;Rapsomanikis, 2015;Collier & Dercon, 2014;Christiaensen et al, 2011;Dercon, 2009;Datt andRavallion, 1998 andVon Braun, 1995 revealed that agricultural commercialisation can be a source of poverty reducing, whereas it aims at adopting agriculture not only to produce food for family's consumption, but also for generating better income by professional applying of technologies and machinery that leads to rising agricultural productivity. The Productivity includes agricultural land and labour which both together are more effective at increasing the incomes of small farmers and poor households who are involved in family farming.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural marketing strategies that encourage commercialization can be an effective way of enhancing agricultural efficiency, raising agricultural household income, and, as a result, improving household food and nutrition security [8]. Furthermore, commercialization may have an impact on dietary improvements and nutrition by expanding the availability of self-produced goods and changing gender roles in the home [9]. Because of this, most developing nations, particularly in West Africa, have made it a major priority in their development plans to include initiatives that might boost agricultural production [7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, to capitalize on the potential benefits of this industry, governments, donor organizations, and even the private sector have made large-scale commercial investments in it [7,10]. There is no question that African agriculture is rapidly commercializing [9]. We analyze literature from the last decades on increasing agricultural sector participation and its implications on poverty reduction and food security in West Africa in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural activities must incorporate agricultural development as one of their primary focuses. Agricultural development is expected to contribute to an increase in this sector's production [2]. The agricultural economy will be able to realize its full potential as a result of agricultural development.…”
Section: Introductionmentioning
confidence: 99%